Brushless DC motor drive with power factor regulation using Landsman converter. Issue 5 (1st April 2016) - Singh, Praveen Kumar; Singh, Bhim; Bist, Vashist
Abstract : This study presents a novel configuration of power factor regulation (PFR)‐based Landsman converter feeding a brushless DC motor (BLDCM) drive for low‐power (400 W) white goods applications. The speed control of the drive is achieved through adjusting the DC bus voltage of voltage source inverter (VSI) feeding to a BLDCM. Moreover, low‐frequency switching signals are used for electronic commutation of BLDCM, which reduces the switching power losses of six solid‐state switches of VSI. This Landsman converter‐based front‐end power factor corrector operating in discontinuous inductor current mode is used to control DC bus voltage and PFR is achieved inherently. The DC bus voltage of the drive is controlled by using a single DC voltage sensor. For evaluating the performance of proposed drive, a prototype is developed in the laboratory. The performance of the BLDCM is also analysed for its operation at varying AC mains voltage (90–265 V). Experiential results for power quality indices are found within the limits of power quality standard IEC 61000‐3‐2.